Innovations in topographically sensitive urban design: evaluating landform conservation strategies in Perth's northern suburbs. Issue 3 (2nd July 2016) - Kullmann, Karl
ABSTRACT: Along Perth's expanding northern coastal corridor, earthwork terracing prepares highly malleable coastal dunes for suburban development. Although local urban design policies of the past decade emphasised the value of conserving and expressing natural topography, terraces and retaining walls remained as the development standard. More recently, topographically responsive planning and design innovations have emerged in several coastal suburban developments. Through four cases studies, the article evaluates the impact of these recent innovations on landform character conservation and suburban planning. The article contributes to the ongoing development of topographically sensitive planning practices, which are pertinent within the global context of increasing coastal suburbanisation.